Dose-Limiting Toxicity After Hypofractionated Dose-Escalated Radiotherapy in Non–Small-Cell Lung Cancer - Cannon, Donald M. (American Society of Clinical Oncology, 2013)
PURPOSE: Local failure rates after radiation therapy (RT) for locally advanced non–small-cell lung cancer (NSCLC) remain high. Consequently, RT dose intensification strategies continue to be explored, including hypofractionation, which allows for RT acceleration that could potentially improve outcomes. The maximum-tolerated dose (MTD) with dose-escalated hypofractionation has not been adequately defined. PATIENTS AND METHODS: Seventy-nine patients with NSCLC were enrolled on a prospective single-institution phase I trial of dose-escalated hypofractionated RT without concurrent chemotherapy. Escalation of dose per fraction was performed according to patients' stratified risk for radiation pneumonitis with total RT doses ranging from 57 to 85.5 Gy in 25 daily fractions over 5 weeks using intensity-modulated radiotherapy. The MTD was defined as the maximum dose with ≤ 20% risk of severe toxicity. RESULTS: No grade 3 pneumonitis was observed and an MTD for acute toxicity was not identified during patient accrual. However, with a longer follow-up period, grade 4 to 5 toxicity occurred in six patients and was correlated with total dose (P = .004). An MTD was identified at 63.25 Gy in 25 fractions. Late grade 4 to 5 toxicities were attributable to damage to central and perihilar structures and correlated with dose to the proximal bronchial tree. CONCLUSION: Although this dose-escalation model limited the rates of clinically significant pneumonitis, dose-limiting toxicity occurred and was dominated by late radiation toxicity involving central and perihilar structures. The identified dose-response for damage to the proximal bronchial tree warrants caution in future dose-intensification protocols, especially when using hypofractionation.